2017
DOI: 10.1186/s12199-017-0610-2
|View full text |Cite
|
Sign up to set email alerts
|

Population profile and residential environment of an urban poor community in Dhaka, Bangladesh

Abstract: ObjectivesA population survey was conducted in an urban shantytown in Bangladesh, as a baseline study of future epidemiological studies. This paper aims to describe the findings of the study, including the population profile and residential environment of the urban poor.MethodsWe conducted a complete count household survey in an urban poor community in Dhaka. Using a brief structured questionnaire in Bengali language, trained interviewers visited each household and asked questions such as: duration of residenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 12 publications
0
33
0
Order By: Relevance
“…Positive attitudes towards patients infected with transmissible diseases represent an essential element in the appropriate care of patients [ 57 ]. Nurses might experience an ethical paradox in deciding whether to provide treatment and care for patients with transmissible diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Positive attitudes towards patients infected with transmissible diseases represent an essential element in the appropriate care of patients [ 57 ]. Nurses might experience an ethical paradox in deciding whether to provide treatment and care for patients with transmissible diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] A study by Zwink N et al showed that parental risk factors such as smoking before conception significantly increased the risk for malformations. [ 24 ] Finally, the proportion of individuals exposed to environmental risk factors (radiation, paint, heavy metals including lead and mercury, and pesticides) was higher in males than that in females (1.46% vs 1.15%), which can be explained by the fact that more males work on jobs related to these factors [ 20 , 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…The population of urban Dhaka was estimated to be approximately 17 million in 2015 [21] and nearly one third of the population Dhaka city inhabit slums [22]. Within the next 14 years the urban population will increase by 50% due to rapid urbanization [23].…”
Section: Introductionmentioning
confidence: 99%